2021
DOI: 10.3390/healthcare9101282
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of RCTs Assessing the Effectiveness of mHealth Interventions to Improve Statin Medication Adherence: Using the Behaviour-Change Technique Taxonomy to Identify the Techniques That Improve Adherence

Abstract: Statin non-adherence is a common problem in the management of cardiovascular disease (CVD), increasing patient morbidity and mortality. Mobile health (mHealth) interventions may be a scalable way to improve medication adherence. The objectives of this review were to assess the literature testing mHealth interventions for statin adherence and to identify the Behaviour-Change Techniques (BCTs) employed by effective and ineffective interventions. A systematic search was conducted of randomised controlled trials (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…The effectiveness of mHealth interventions on cardiovascular medication adherence has also been reported in other systematic reviews, which showed that the majority of studies reported an improvement in medication adherence and other health outcomes [ 39 , 40 ]. Similar findings from an existing body of literature strengthen the current review’s evidence [ 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 89%
“…The effectiveness of mHealth interventions on cardiovascular medication adherence has also been reported in other systematic reviews, which showed that the majority of studies reported an improvement in medication adherence and other health outcomes [ 39 , 40 ]. Similar findings from an existing body of literature strengthen the current review’s evidence [ 41 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 89%
“…More research has been performed on how to improve statin adherence than on how to improve statin initiation, but nudges for other conditions may serve as a guide. In previous work, nudges delivered to patients by text message in the days preceding a primary care visit significantly increased influenza vaccination .…”
Section: Introductionmentioning
confidence: 99%
“…Medications of interest within the 80 reviews included in our umbrella review were: statins (n=10),25–34 antihypertensives (n=38),35–72 and statins and antihypertensives (n=34) 73–104. Nine of the reviews synthesised qualitative evidence,27 31 42 50 55 58 60 61 83 104 four of which also included quantitative evidence in a mixed evidence synthesis 42 50 58 61.…”
Section: Resultsmentioning
confidence: 99%
“…Nine of the reviews synthesised qualitative evidence,27 31 42 50 55 58 60 61 83 104 four of which also included quantitative evidence in a mixed evidence synthesis 42 50 58 61. Of the reviews synthesising quantitative evidence evaluating interventions, interventions focused on: enhancing patient adherence to medication as prescribed (n=57),25 30 32–35 37–41 43–46 48 49 51 53 54 56 57 59 62 63 65–71 73–81 86 87 89–96 98–103 105 deprescribing a prescribed medication (n=6)36 46 72 80 88 93 or optimising the prescribing of medication to meet the needs of the patient (n=13) 26 28 29 38 52 64 71 84 85 87 90 100 106. Three of these reviews were judged by reviewers to have dual aims 71 87 90.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation